2000
DOI: 10.1149/1.1393163
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of Thin Cation-Exchange Membranes Using Glow Discharge Plasma Polymerization and Its Reactions

Abstract: Thin cation-exchange films with fixed sulfonic acid groups were prepared by plasma polymerization followed by hydrolysis of sulfonyl halide groups using benzenesulfonyl fluoride and benzenesulfonyl chloride as starting materials. For benzenesulfonyl fluoride, sulfonyl fluoride groups were introduced into the plasma-formed polymers, whereas benzenesulfonyl chloride tended to decompose during plasma polymerization. The difference between the reaction in the glow discharge plasma of benzenesulfonyl fluoride and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 39 publications
0
18
1
Order By: Relevance
“…Due to their large variety of chemical and physical properties, these films have been proposed for very different applications. Otherwise, because of the strong dependence on the deposition properties of films made from these and other monomers, it has been reported that they can also be used as gas separation layers or gas permeation layers [43,[62][63][64][65][66][67][68][69][70][71][72]. Organosilicon monomers like hexamethyldisilazane (HMDSN), hexamethyldisiloxane (HMDSO), vinyltrimethylsilane (VTMS), tetramethylsilane (TMS) or various other silanes, but also ethanes and ethenes as well as fluorocarbons like perfluorobenzene were the main components used.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…Due to their large variety of chemical and physical properties, these films have been proposed for very different applications. Otherwise, because of the strong dependence on the deposition properties of films made from these and other monomers, it has been reported that they can also be used as gas separation layers or gas permeation layers [43,[62][63][64][65][66][67][68][69][70][71][72]. Organosilicon monomers like hexamethyldisilazane (HMDSN), hexamethyldisiloxane (HMDSO), vinyltrimethylsilane (VTMS), tetramethylsilane (TMS) or various other silanes, but also ethanes and ethenes as well as fluorocarbons like perfluorobenzene were the main components used.…”
Section: Plasma Polymerizationmentioning
confidence: 99%
“…In combination with other thin film processes (e.g., sputter deposition of the catalyst material), a membrane electrode assembly (MEA) of miniaturized DMFCs can be realized in successive deposition steps which have the potential to improve the three-phase boundary (membrane, electrode, and catalyst) and improve the performance of DMFCs. In addition, this technique allows large scale fabrications of membrane electrode assemblies at low cost [14][15][16][17][18]22,23].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Today, research groups working on that subject remain very few, and their published results are, as yet, not as good as those obtained with conventional membranes. [7][8][9][10][11][12][13][14][15][16] Previous studies by our group, published in journals in the field of membranes or fuel cells, have focused on the description of the plasma polymerization technique (principle and apparatus) and presentation of many detailed results relative to the fragmentation of monomers in plasma reactors (using mass spectrometry analysis), the microstructural (morphology, density, chemical structure) and transport properties (ionic conductivity, ion transport number, fuel sorption, and permeability) of plasma-polymerized membranes; some correlations between the plasma synthesis parameters and the material properties have been established. [17][18][19] These works have shown that it is possible to synthesize plasma-polymerized membranes presenting very interesting properties (high compactness, good chemical and thermal stability, satisfying ionic conduction level, and very low permeability to fuel) for application in miniaturized fuel cells.…”
Section: Introductionmentioning
confidence: 99%